A South Asian vernacular public overseas: Tamil in the Straits Settlements, c. 1870-1942 - Tschacher, Torsten (Language ideologies and the vernacular in colonial and postcolonial South Asia, 2023)
The idea of a ‘South Asian vernacular’ during the colonial period conjures up the idea of a relatively simple language hierarchy, with English as the dominant idiom of colonial power, a few privileged South Asian vernaculars recognized by the colonial government, and a large number of languages that did not receive any public support. But how did this language-hierarchy look from the perspective of South Asians settled overseas, as traders or laborers in another colony? How were South Asian publics constituted in conditions that were different from those at home? In how far were patterns reproduced or changed? And what language ideologies were formulated in the diaspora, in comparison to developments in South Asia? One interesting case to consider these questions is the development of Tamil print and publishing in the Straits Settlements (Singapore, Penang, and Melaka) between the late nineteenth century and the Japanese occupation in 1942. From the 1870s onward, Tamil newspapers and books began to be published locally, mostly by Muslim printers. Until World War I, Tamil publishing in the Straits Settlements largely followed local patterns. After the war, the situation changed, and with the impact of both Indian and Dravidian nationalism, the local Tamil public sphere became more ‘diasporic’ in the sense that it became more dependent on discourses produced in India.